DEVELOPMENT OF AN AUGMENTED REALITY APPLICATION FOR LEARNING THE VOLUME AND SURFACE AREA OF THREE-DIMENSIONAL SHAPES - Andy Sapta; Sondang Purnamasari Pakpahan (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
This study focuses on the development of an Augmented Reality (AR)–based learning application designed to assist students in understanding the mathematical concepts of volume and surface area of three-dimensional geometric shapes. The development process adopted the Multimedia Development Life Cycle (MDLC) model, which consists of six systematic stages: concept, design, material collecting, assembly, testing, and distribution. The research concentrated on the development and expert validation stages. Validation results from content and media experts indicate that the application meets pedagogical and technical feasibility standards. The content expert confirmed that the materials align with the national mathematics curriculum and are presented in a clear, contextual, and accurate manner, while the media expert highlighted the user-friendly interface, interactive features, and visual appeal of the application. Theoretically, this AR-based medium bridges the gap between abstract mathematical concepts and concrete visualization by enabling students to interact directly with virtual 3D objects. Practically, the application enhances learning motivation and engagement by providing dynamic, interactive experiences. Overall, this research contributes to the advancement of educational technology by offering a systematic model for developing AR-based learning media that support active and meaningful learning in the digital era.